Labor informality bias of a poverty-alleviation program in Argentina - Gasparini, Leonardo Carlos (2009)
In 2002, in the midst of a serious macroeconomic crisis, Argentina implemented a large social program (the Programa Jefes de Hogar, PJH) that provides cash transfers to unemployed household heads meeting certain criteria. In practice, the difficulty in monitoring the unemployment requirement for informal (unregistered) workers would imply a disincentive for the program participants to search for a formal job. By applying matching techniques we evaluate the empirical relevance of this prediction during the period of strong economic growth that followed the crisis. We find some evidence on the informality bias of the PJH when the value of the cash transfer was relatively high compared to wages in the formal labor market.